CONDITIONS IN THE FEMALE PRISION AND THE FRAGILITY OF FUNDAMENTAL RIGHTS - Daiana Oliveira Silva, Laura (Revista Gênero e Interdisciplinaridade, 2022)
The present work proposes to investigate the conditions of women’s penitentiaries, verifying if the rights protectyed to women are carried out. Will be investigated the healt, the infrastructure, the hygiene, and the psychological aspect. About dignity of the human person, the prisional conditions in confrontation to constitution and international treaties. There will be an elucidation of the matherhood, the gestation, the postpartum and child development within the prison. Finally, the debate on public policies, how are applied, as well as their effectiveness. To this end, an exploration of legislation, doctrine, articles, and official data on female incarceration was carried out.